Manajemen Mutu Pendidikan Agama Islam dalam Mengatasi Kesenjangan antara Prestasi Akademik dan Pembentukan Karakter Peserta Didik (Studi Literatur) - Agus Nuril Anwar; Muhammad Husni (Jurnal Manajemen dan Ilmu Administrasi, 2026)
Islamic Religious Education (IRE) plays an essential role in developing students’ intellectual, spiritual, and moral competencies. However, contemporary educational practices indicate that educational success is still predominantly measured through academic achievement rather than character formation. This study aims to analyze the gap between academic achievement and character building in Islamic Religious Education from the perspective of Islamic educational quality management. The research employed a qualitative approach using a literature review method. Data were collected from national indexed journals and reputable international publications published between 2020 and 2026 through databases such as Google Scholar, Garuda, Crossref, and DOAJ. The collected literature was analyzed using content analysis techniques through data reduction, thematic classification, interpretation, and conclusion drawing. The findings reveal that the dominance of academic orientation, the weak integration of character education within quality management systems, and the lack of consistent religious school culture contribute significantly to the imbalance between cognitive achievement and students’ moral development. The study also found that hidden curriculum, teachers’ role modeling, and transformational leadership play important roles in strengthening students’ character formation. Therefore, Islamic educational quality management requires a holistic and integrative reorientation that combines academic excellence with spiritual, moral, and social character development through religious culture, comprehensive evaluation systems, and collaborative educational environments.